2014
DOI: 10.1016/j.cub.2014.05.031
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Gap Detection Is Mediated by Gap Termination Responses in Auditory Cortex

Abstract: Background Understanding speech in the presence of background noise often becomes increasingly difficult with age. These age-related speech processing deficits reflect impairments in temporal acuity. Gap detection is a model for temporal acuity in speech processing, in which a gap inserted in white noise acts as a cue that attenuates subsequent startle responses. Lesion studies have shown that auditory cortex is necessary for the detection of brief gaps, and auditory cortical neurons respond to the end of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
113
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(123 citation statements)
references
References 46 publications
8
113
0
2
Order By: Relevance
“…For example, decreased forward suppression may be important for detecting gaps in noise—an important component of interpreting speech in noise—because it has recently been shown that increasing cortical responses after brief gaps (which would effectively reduce forward suppression) increases the ability to detect gaps (Weible et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…For example, decreased forward suppression may be important for detecting gaps in noise—an important component of interpreting speech in noise—because it has recently been shown that increasing cortical responses after brief gaps (which would effectively reduce forward suppression) increases the ability to detect gaps (Weible et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Weible et al . () found that suppressing cortical neural activity using optogenetics following a gap could attenuate subsequent behavioural startle responses for gaps with durations of ≤ 25 ms, but not for 50 ms gaps (the duration used here), which further suggests that cortical involvement is important only for shorter durations. Therefore, the effect on gap‐induced reductions of cortical evoked potentials that we have observed here may simply be a reflection of processing further down the auditory system.…”
Section: Discussionmentioning
confidence: 99%
“…Weible et al . () recently demonstrated that they could affect the degree of startle attenuation (as measured behaviourally) by using optogenetics to alter inhibitory and excitatory activity in the auditory cortices of mice, while preserving MGDTs. This therefore implies that there may be disparate underlying mechanisms between gap detection thresholds, which they suggested are a measure of temporal acuity, and inhibition of a startle response by a preceding gap, which they proposed as a measure of gap salience.…”
Section: Introductionmentioning
confidence: 97%
“…After the fitting of cochlear implants, some of these patients have been reported to face unusual speech-recognition difficulties not observed in patients with mutations of other deafness genes (53). These difficulties might be related to the involvement of PV interneurons in the experience-driven neural plasticity underlying AC maturation (8,54) and the temporal precision of sound detection critical for speech perception (55). The shaping of the perception of several acoustic features throughout life, including frequency discrimination acuity (56) and the detection of unexpected sounds, also involves PV interneurons of the AC (57).…”
Section: Discussionmentioning
confidence: 99%